Dynamics of muscle blood flow, O[subscript2] uptake and muscle microvascular oxygenation during exercise - Ferreira, Leonardo Franklin (Kansas State University, 2006)
The overall aim of this dissertation is to better understand the dynamic matching between O2 delivery and uptake following the onset of exercise. The first study of this dissertation (Chapter 2) revealed that: i) the dynamics of muscle oxygenation were determined primarily by the QO2–VO2 interaction during the initial phase of QO2 response (first 15-20 s); and ii) absolute values in the steady state used to calculate blood flow from VO2 and O2 extraction did not affect the dynamics of blood flow response. Consistent with these predictions, using pulmonary gas exchange and near-infrared spectroscopy in humans (Chapter 3) we observed that the estimated kinetics of capillary blood flow (moderate exercise 25.4 ± 9.1 s and heavy exercise 25.7 ± 7.7 s) were not significantly different from the kinetics of muscle VO2 (moderate exercise 25.5 ± 8.8 s and heavy exercise 25.6 ± 7.2 s). In Chapter 4 we observed that nitric oxide (NO) is essential to maintain microvascular O2 pressure (PO2mv ~ QO2/VO2) of contracting rat muscles. Blockade of NO synthase with L-NAME accelerated the kinetics [ΔMean response time(L-NAME–CONTROL) = -6.5 ± 6.6 s, P< 0.05] and reduced the contracting steady-state PO2mv [ΔPO2mv(L-NAME–CONTROL) = -5.0 ± 1.0 mmHg; P < 0.05] compared to control. In Chapter 5 we focused on the kinetics of bulk limb blood flow (LBF) to show that a low-pass filter (LPFILTER) developed for LBF data improved the confidence of kinetic analysis by decreasing the standard error of the estimate (SEE ~ 95% confidence interval) for all kinetics parameters compared to the Beat-by-Beat method (e.g., time-constant phase 2: Beat-by-Beat = 16 ± 5 s; LPFILTER = 1.1 ± 0.5 s). In conclusion, the early increase in QO2 is the main determinant of muscle oxygenation dynamics and NO is essential to maintain the tight coupling of QO2 and VO2 kinetics during exercise. In this context, application of a LPFILTER to LBF data provides the best confidence for kinetic analysis of bulk QO2 that should facilitate investigations integrating bulk and microvascular QO2/VO2 matching in a variety of settings in health and disease.
Keywords: Oxygen; Muscle; Exercise; Physiology; Biology, Animal Physiology (0433); Health Sciences, General (0566)